Measurement and Characterization of Natural Radioactive Contaminants and Industrial for the Sediments Diyala River Basin with Using Gamma-Ray Spectroscopy - Nasif, Raad M.; Mkhaiber, Ahmed F.; Younis, Duraid H.; Subhi, Auday T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, we have achieved the description of radionuclides that exist in the samples of Diyala river sediments as well as to measure the specific activities using gamma-ray spectroscopy. The eleven samples were collected among the length of Diyala River starting from Al- Rustumiya and finishing at the point where Diyala River meets Tigris which is in Baghdad.      Gamma-ray spectrometry system consists of high-purity germanium detector (HpGe) with 50% efficiency and resolution (2.2 keV) for the energy (1332 keV) was used for standard source 60Co.     Card spectrum analyzer connected to the PC type Pentium 4 was used to view the spectrum. And  rates of the specific activity for the radionuclides, (214Bi) Equivalent to the specific activity of 238U and (228Ac) Equivalent to the specific activity of 232Th and (40K) in these sediments are (29.997 Bq / kg) and (13.74 Bq / kg) and (839.85 Bq / kg), respectively.In addition to that (4.85 Bq / kg) for nuclide 137Cs. Calculations showed that hazard index  (H) for these radionuclides was (0.389 Bq / kg), which is within the allowable limit being less than 1, and approach to recorded some international organizations such as the (WHO) , (ICRP) , (NCRP) and (EPA ) which are within maximum allowed.